Correlation between Nurses’ Knowledge Level and Their Skill in the Administration of Basic Life Support (BLS) at General Hospital of HKBP Balige - Connie Melva Sianipar (Benih : Journal of Midwifery, 2025)
Emergency nursing is a comprehensive nursing care provided to patients with life-threatening medical conditions. Emergency Nursing connects the knowledge and skill to deal with patients with life-threatening medical conditions. The objective of this research is to investigate the correlation between nurses’ knowledge and their skill in the administration of the BLS at General Hospital of HKBP Balige. This research used the descriptive correlational method. It was conducted at General Hospital of HKBP Balige. The samples of research were 30 respondents and were taken by using the purposive sampling technique. The data were analyzed by using the Spearman’s Rank analysis. The result of this research shows that 23 respondents (76.6%) had fair knowledge, and 22 respondents (73.4%) had fair skill as indicated by the p-value = 0.000 and the r-value = 0.677. Thus, there was a strong correlation with the positive r-value between the nurses’ knowledge and their skill in the administration of the BLS at General Hospital of HKBP Balige. Thus, the health service providers need to improve their knowledge and skill about the BLS by holding seminar or training.